2000
DOI: 10.1007/pl00008676
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in CDC14 result in high sensitivity to cyclin gene dosage in Saccharomyces cerevisiae

Abstract: We screened for mutations that resulted in lethality when the G1 cyclin Cln2p was overexpressed throughout the cell cycle in Saccharomyces cerevisiae. Mutations in five complementation groups were found to give this phenotype, and three of the mutated genes were identified as MEC1, NUP170, and CDC14. Mutations in CDC14 may have been recovered in the screen because Cdc14p may reduce the cyclin B (Clb)-associated Cdc28 kinase activity in late mitosis, and Cln2p may normally activate Clb-Cdc28 kinase activity by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
13
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 66 publications
5
13
0
Order By: Relevance
“…GAL-SIC1 cdc14-1 CLB3 cells were viable up to 30°with GAL-SIC1 off (YEPD), and were rescued weakly at higher temperatures with GAL-SIC1 on (YEPG), consistent with previous observations (Jaspersen et al 1998;Yuste-Rojas and Cross 2000). GAL-SIC1 cdc14-1 CLB3Ddb cells were inviable at all tested temperatures with GAL-SIC1 off, and were rescued with GAL-SIC1 on up to 27°(with partial rescue at 30°).…”
Section: Fully Functional Cdc14 Is Required For Viability In the Absesupporting
confidence: 90%
See 1 more Smart Citation
“…GAL-SIC1 cdc14-1 CLB3 cells were viable up to 30°with GAL-SIC1 off (YEPD), and were rescued weakly at higher temperatures with GAL-SIC1 on (YEPG), consistent with previous observations (Jaspersen et al 1998;Yuste-Rojas and Cross 2000). GAL-SIC1 cdc14-1 CLB3Ddb cells were inviable at all tested temperatures with GAL-SIC1 off, and were rescued with GAL-SIC1 on up to 27°(with partial rescue at 30°).…”
Section: Fully Functional Cdc14 Is Required For Viability In the Absesupporting
confidence: 90%
“…To test for viability of CLB3Ddb cells with lowered Cdc14 activity, we used the temperature-sensitive allele cdc14-1 (Hartwell et al 1974), which can be partially rescued at nonpermissive temperature by overexpressed SIC1 (Jaspersen et al 1998;Yuste-Rojas and Cross 2000). We made 103 serial dilutions of CDC14 CLB3, CDC14 CLB3Ddb, cdc14-1 CLB3, and cdc14-1 CLB3Ddb cells (all bearing GAL-SIC1) on YEP-Glucose ("YEPD"; GAL off) and YEP-Galactose ("YEPG"; GAL on) plates, and placed them at various temperatures ( Figure 5A).…”
Section: Fully Functional Cdc14 Is Required For Viability In the Absementioning
confidence: 99%
“…Similar to all known initiation mutants reported, the plasmid loss of cdc14-1 cells could be suppressed by adding multiple copies of an ARS to the plasmid (Hogan & Koshland, 1992;Ma et al, 2010). Overexpression of the initiation protein Orc6p caused synthetic dosage lethality in cdc14-1 cells (Kroll et al, 1996), and synthetic lethality was observed when cdc14-1 was combined with cdc6-1, orc2-1 or orc5-1 (Loo et al, 1995;Kroll et al, 1996;Yuste-Rojas & Cross, 2000). Orc6p was found to be dephosphorylated by www.intechopen.com (Bloom & Cross, 2007).…”
Section: Linkage Between Cdc14p and Dna Replication Initiationmentioning
confidence: 75%
“…The cdc14-1 mutant arrests in telophase at its restrictive temperature of 37°C, but even at its permissive room temperature (25°C), this mutant is still hypomorphic because it shows synthetic lethal genetic interactions with various mutants, unlike CDC14 (Jaspersen et al. , 1998; Yuste-Rojas and Cross, 2000; Rossio et al. , 2010; Zhai et al.…”
Section: Resultsmentioning
confidence: 99%